Descriptive Analysis of Questions in the 2013 Curriculum Textbook (2018 Revised Edition) for Grade IX SMP/MTs Mathematics Lessons in Terms of the 2019 TIMSS Cognitive Domain - Tayeb, Thamrin; Idris, Ridwan; Halimah, Andi; Nursalam; Lira, Qualan Ma’ruf (Department of Mathematics Education, 2024)
This study aims to determine the proportion of questions in the 2013 curriculum student book for Mathematics grade IX SMP/MTs that are categorized in the TIMSS cognitive domains compared to the proportion of TIMSS 2019 standards. This type of research uses descriptive qualitative research. The research instrument used was the assessment framework guidelines that have been provided in the TIMSS 2019 book. The research process began with an analysis of the questions contained in the Mathematics student book for grade IX SMP/MTs which was conducted independently by the researcher. The results showed that from 344 valid items contained in the Mathematics student book for grade IX SMP/MTs, the percentage of “knowing” cognitive domain in the book was 37.68%, compared to the standard set by the TIMSS 2019 assessment criteria of 35%. Then, the percentage of “applying” cognitive domain in the book is 52.21%, compared to the standard set by TIMSS 2019 assessment criteria of 40%. Meanwhile, the percentage of “reasoning” cognitive domain in the book was 10.11%, compared to the standard set by the TIMSS 2019 assessment criteria of 25%.